SOLID-STATE PROPERTIES AND SOLUBILITY STUDIES OF NOVEL PHARMACEUTICAL COCRYSTAL OF ITRACONAZOLE - Hiendrawan, Stevanus; Veriansyah, Bambang; Tjandrawinata, Raymond R. (International Journal of Applied Pharmaceutics, 2018)
Objective: Pharmaceutical cocrystal is a promising method to improve the solubility of active pharmaceutical ingredients (APIs). Itraconazole (ITZ) is a BCS class II antifungal drug with poor aqueous solubility, therefore an attempt was made to improve the solubility of ITZ using cocrystallization technique. In this work, six novel pharmaceutical cocrystals of ITZ with various coformers, including 4-hydroxybenzoic acid (4HBA), trans-cinnamic acid (TCA), suberic acid (SUB), sebacic acid (SBC), 1-hydroxy-2-naphthoic acid (1H2N), and benzamide (BZD) were prepared. Methods: ITZ cocrystals was prepared by solvent evaporation process. The cocrystals produced were characterized using powder x-ray diffraction (PXRD), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and fourier transform infrared (FTIR) spectroscopy. Solubility analysis was performed to evaluate the cocrystals. Results: PXRD and DSC analysis revealed that the pattern of all ITZ cocrystals was distinguishable from the individual compounds which indicates the formation of new phase. The solubility of ITZ and its cocrystals from highest to lowest after 24 h in 0.1 N HCl solution (pH 1.2) follows the order ITZ-TCA (1.97-fold), ITZ-SBC (1.09-fold), ITZ, ITZ-1H2N (0.58-fold) and ITZ-4HBA (0.46-fold). Conclusion: This study demonstrates that the selection of coformers has pronounced an impact on the physicochemical properties of ITZ. Based on this study, it can be concluded that cocrystallization offers a valuable way to improve the solubility of ITZ.